A social encouragement in risk awareness using volunteered geographic information and scenario-based analysis - CHOMCHANOK ARUNPLOD (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research’s main contribution is a social analysis of volunteered geographic information for Thais that uses mapping technology and scenario-based analysis. The community’s safety depends on its members having a thorough understanding of potential threats. It has yet to be widely acknowledged, especially in urban and industrial areas.Method: Both the geographic data and the statistical data associated with the local community are gathered from publicly available sources. The community risk map was created through spatial analysis. In this context, the map serves as a means of communication.Findings: The study results show that locals are aware of the dangers they face and are motivated to take action to reduce their risk. Population counts and social conditions can be inferred using demographic data from an open spatial point dataset, making this information essential for risk management and community issues.Implications/Novel Contribution: This research fills a gap in the literature by providing empirical evidence that social and demographic data can be derived from publicly available sources.